Medical therapy reduces microbiota diversity and evenness in surgically recalcitrant chronic rhinosinusitis. Issue 10 (10th July 2013) - Liu, Cindy M.; Soldanova, Katerina; Nordstrom, Lora; Dwan, Michael G.; Moss, Owain L.; Contente‐Cuomo, Tania L.; Keim, Paul; Price, Lance B.; Lane, Andrew P.
Abstract : Background: Chronic rhinosinusitis (CRS) is a highly prevalent and heterogeneous condition frequently treated with antibiotics and corticosteroid therapy. However, the effect of medical therapy on sinus microbiota remains unknown. Methods: We enrolled CRS patients (n = 6) with patent maxillary antrostomies and active mucosal inflammation, who had not received antibiotics or corticosteroids in the previous 8 weeks. A pretreatment and posttreatment maxillary sinus swab was collected, from which DNA was extracted, pyrosequenced, and analyzed using a naïve Bayesian classifier and ecological analyses. Results: Four patients showed significant improvement in endoscopic appearance. The shifts in microbiota in response to therapy were highly individualized. There was no single common microbiota profile among patients with similar clinical outcomes, but overall there was significant decrease in microbiota diversity ( t (5) = 2.05, p = 0.10) and evenness ( t (5) = 2.28, p = 0.07) after treatment. Conclusion: Our findings strongly correlate with earlier studies that examined the impact of antibiotics on human microbiota. We observed that posttreatment, patients frequently became colonized by taxa that are less susceptible to the prescribed antibiotics. Our findings highlight the challenge in seeking generalizable diagnostic and therapeutic options in CRS, particularly regarding microbiological response and outcomes.